A Single Dose Thymoglobulin in Non-Sensitized Deceased Donor Kidney Recipients >60 Years. (July 2018) - Mor, Eytan; Nesher, Eviatar; Eizner, Sigal; Gurevich, Michael; Mehjibovsky, Vadym; Tennak, Vladimir; Rahamimov, Ruth
Abstract : In low risk patients (non-sensitized 1st transplant) induction protocol using interlukin-2 receptor antagonist is a standard protocol in many transplant centers. We recently changed our protocol and used a single dose thymoglobulin that offers lymphocyte deletion for the first 2-3 days post-transplant allowing to achieve target tacrolimus levels by then. We sought to determine the efficacy and safety of our protocol in first transplant non-sensitize patients >60 years. Materials and Methods: We studied two consecutive cohorts of 136 patients > 60 years receiving Simulect (group 1) and Thymoglobulin (group 2). Fifty four patients in group 1 transplanted between 5/2011- 3/2014 received two doses of 20 mg Simulect (day 0 and 4). Eighty two patients in group 2 transplanted between 4/2014-3/2017 received a single dose of 1-1.5mg/kg Thymoglobulin. We compared their base-line demographic and clinical characteristics and analyzed the outcome including incidence of ATN, rejection, viral infection and patient and death censored graft survival. Results: The mean age in group 1 and group 2 was 65.7 and 66.2 yr., respectively (ns). The mean donor age was 61.5 and 61.1 yr. respectively (ns). There was no difference in weight, male/female ratio, rate of DM, heart disease and DR mismatch between the two groups. Ischemic time was 11.2 vs. 9.8 hr. in group 1 and 2, respectively (p=0.034). The ATN rate in group 2 was 26.8% vs. 38.8% (ns). Biopsy proven rejection was noted in 6 patients in group 1 (11.1%) and 6 (7.3%) in group2 (ns). There was no significant difference in the incidence of polyoma and CMV infection between the two groups. Patient survival at 1- and 3 yr. was 92.6% and 85% for group 1 and 95% and 88.5% for group 2 (ns). Death-censored graft survival at 1- and 3 years was 88.5% and 88.5% vs. 98.8% and 83.6%, for group 1 and group 2, respectively (p=0.06). Conclusion: A single dose thymoglobulin is an effective induction protocol for low risk kidney transplant recipients> 60 years.